LiBr passivation effect of porous nanocrystalline hydrogenated silicon. (December 2015) - Amor, Sana Ben; Haddadi, Ikbel; Seif, El Whibi; Daik, Ridha; Bousbih, Rabaa; Dimassi, Wissem; Ezzaouia, Hatem
Abstract: Nanocrystalline hydrogenated silicon (nc-Si:H) films were deposited on a p-type silicon substrate by plasma enhanced chemical vapor deposition (PECVD), using SiH4 and H2 as reactive gases. Porous (nc-Si:H) layers were afterward obtained and immersed in a lithium bromide (LiBr) aqueous solution in order to enhance their optical and electrical properties for a potential solar cells application. A decrease in the reflectivity to about 9% for Li/porous nc-Si:H layer deposited at 75 sccm against an increase in the minority carrier lifetime were obtained. We correlate these results to the change in crystalline characteristics and chemical composition of the layers in order to understand the effect of LiBr coating on nc-Si:H Through optical and electrical characterization we have demonstrated the possibility of using such LiBr treatment to improve the properties of porous nc-Si:H. Highlights: The immersion in LiBr solution of nc-Si:H films grown at different hydrogen flow rates. The microstructure of the different films is analyzed. The study of the effect of LiBr treatment on volume fraction, crystal size. The variation of the reflectivity was investigated. The effect of LiBr treatment on the minority carrier lifetime.